2011
DOI: 10.1002/bdm.729
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Dynamics of Cooperation

Abstract: Parties in real-world conflicts often attempt to punish each other's behavior. If this strategy fails to produce mutual cooperation, they may increase punishment magnitude. The present experiment investigated whether delay-reduction -potentially less harmful than magnitude increase -would generate mutual cooperation as interactions are repeated. Participants played a prisoner's dilemma game against a computer that played a tit-for-tat strategy, cooperating after a participant cooperated, defecting after a part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 30 publications
1
10
0
1
Order By: Relevance
“…One answer relies on socially discounted rewards, the other on delay discounted rewards. With respect to delay, Locey and Rachlin (2012) found that when delay of PD-game reciprocation was explicitly varied, cooperation varied inversely with delay. Although the present experiment did find a significant correlation between P’s cooperation and stated closeness to OP, and failed to find any evidence of direct reciprocation of cooperation (on the immediately following trial), there was a strong, significant correlation between cooperation by P and OP for both groups – stronger for the group that cooperated more (1-2-9-10).…”
Section: Discussionmentioning
confidence: 99%
“…One answer relies on socially discounted rewards, the other on delay discounted rewards. With respect to delay, Locey and Rachlin (2012) found that when delay of PD-game reciprocation was explicitly varied, cooperation varied inversely with delay. Although the present experiment did find a significant correlation between P’s cooperation and stated closeness to OP, and failed to find any evidence of direct reciprocation of cooperation (on the immediately following trial), there was a strong, significant correlation between cooperation by P and OP for both groups – stronger for the group that cooperated more (1-2-9-10).…”
Section: Discussionmentioning
confidence: 99%
“…Cooperative dilemmas pit the costs associated with sharing one's resources against the benefits that sharing creates for others. Given that cooperation is such an essential aspect of daily life (as well as a necessary condition for the continued survival of humankind), a great deal of research across psychology, economics, sociology, and biology has tried to understand and model how people make cooperation decisions (Apicella, Marlowe, Fowler, & Christakis, ; Axelrod, ; Bazerman, Magliozzi, & Neale, ; Bereby‐Meyer & Roth, ; Bicchieri & Xiao, ; Crockett, ; Dawes, McTavish, & Shaklee, ; DeSteno, ; Fiedler, Glöckner, Nicklisch, & Dickert, ; Frank, Gilovich, & Regan, ; Fudenberg & Maskin, ; Fudenberg, Rand, & Dreber, ; Galinsky & Mussweiler, ; Gray, Ward, & Norton, ; Halevy, Weisel, & Bornstein, ; Locey & Rachlin, ; Pfeiffer, Tran, Krumme, & Rand, ; Rand & Nowak, ; Sanfey, Rilling, Aronson, Nystrom, & Cohen, ; Van den Bos, Vermunt, & Wilke, ; Zaki & Mitchell, ). Economic games have become a standard paradigm for exploring cooperation across fields because of their simple quantification of cooperativeness and their use of actual behavior rather than self‐report measures or hypothetical scenarios (Camerer & Fehr, ).…”
mentioning
confidence: 99%
“…As expected, in the second scenario where the possibility to be rewarded immediately was eliminated, the level of cooperation was higher. Another method of affecting the discounting process was used by Locey and Rachlin (2012) in the study performed on people. The method involved manipulation of the time between the player's choice to the partner's reply (the partner being a computer following the "tit for tat" strategy).…”
Section: Fig 1 Payoff Matrix Of 2-person Prisoner's Dilemma Game (Pmentioning
confidence: 99%